Après Nous le Déluge? Direct Democracy and Intergenerational Conflicts in Ageing Societies - Gabriel Ahlfeldt; Wolfgang Maennig; Malte Steenbeck (Center for Economic Studies and ifo Institute (CESifo), 2016)
To assess the likely effects of population ageing on the outcomes of direct democracy, we analyze the effect of age on voting decisions in public referenda. To this end, we provide the first quantitative review of the literature and a case study of the Stuttgart 21 referendum on one of the largest infrastructure projects in Germany. The evi-dence suggests that intergenerational conflicts arising from population ageing will likely be limited to areas in which the net present value differs particularly strongly across generations, such as education and health spending, green energy, and major transport projects. In such instances, however, the effect can be quantitatively relevant, raising the question of whether, as population ageing progresses, decisions should be based on social cost-benefit analyses, instead of referenda.
Keywords: D61; D62; H41; H71; L83; I18; R41; R58; 330; ageing; direct democracy; intergenerational conflict; NIMBY; referendum; Stuttgart 21; transport; voting